Volume 8C: Heat Transfer and Thermal Engineering 2013
DOI: 10.1115/imece2013-62350
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation to Evaluate the Performance of Helical Coiled Tube Heat Exchanger With and Without Nanofluid

Abstract: A numerical analysis presented out to simulate internal forced convection and temperature distribution in helical coil tube with and without nanofluid. An ANSYS FLUENT package 14.1 commercial copy with SOLID WORK and GAMBIT software program is employed. The flow pattern and temperature distribution in helical coil tube heat exchanger is studied with and without nanofluid. Numerical work included two parts: the first is included helical coil heat exchanger with optimum curvature ratio (17). An optimum helical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Unfortunately, it has been observed that metal foam decreases the influence of natural convection at the phase change processes. Mahdi et al [5] experimentally studied the melting phenomena of paraffin wax in a conical coil thermal energy storage unit (TES). The obtained results indicated that TES with the conical coil, compared with the helical coil type, significantly enhances heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it has been observed that metal foam decreases the influence of natural convection at the phase change processes. Mahdi et al [5] experimentally studied the melting phenomena of paraffin wax in a conical coil thermal energy storage unit (TES). The obtained results indicated that TES with the conical coil, compared with the helical coil type, significantly enhances heat transfer.…”
Section: Introductionmentioning
confidence: 99%